Islam dan Feminisme: Telaah Atas Teologi Feminisme - Zainul Fanani (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2007)
This study aims to analyze the relationship between Islam and feminism through an examination of feminist theology. This study explores how the principles of feminism are interpreted in Islamic discourse and the extent to which the concept of gender justice can be harmonized with Islamic teachings. The method used is library research with a descriptive-analytical approach, which examines various Islamic and feminist literature, both from the perspective of Muslim academics and feminist thinkers. The results show that there are differences of opinion in understanding feminism in Islam, with some seeing it as an attempt to reconstruct equality-based theology, while others consider it to be contrary to Islamic teachings. This study emphasizes that the dialogue between Islam and feminism can open up space for reinterpretation of religious texts while maintaining Islamic values. This study contributes to enriching the discourse on gender justice from an Islamic perspective.